Nationallizenzen aus Sicht und im Förderspektrum der Deutschen Forschungsgemeinschaft (DFG): Grundlagen und Einbindung in die Förderstrukturen / National licences from the point of view and in the funding spectrum of the Deutsche Forschungsgemeinschaft (DFG): basic principles and embedding into the structures of funding - Rutz, Reinhard (GMS Medizin – Bibliothek – Information, 2007)
The Deutsche Forschungsgemeinschaft (DFG) ist the biggest third-party research funding organisation in Germany. In 2007 it supplied 15 Million Euro for national licences for archived digital content and for the first time 18.5 Million Euro for national licences for current subscriptions of e-journals in oder to support research information infrastructure. The paper describes DFG's aims and the hithero installation process of national licences funding program since 2004. Furthermore a basic outline of the focus initiative "Digital Information 2008-2012" will be given. The initiative is part of DFG's system of nationwide literature supply for research purposes which includes support for the important area of special subject collections. This system is funded by the DFG since decades.